Asphalt mixtures produced with 100% reclaimed materials - Oliveira, Joel (2011)
The environmental and economic benefits of using Reclaimed Asphalt Pavement (RAP) material in hot mix asphalt (HMA) applications could be pushed up to the limit, by producing totally recycled HMAs (100% RAP), but the performance of this alternative must be satisfactory. In fact, these mixtures could possibly present a lower performance due to the behaviour of the aged binder, which loses its lighter fractions with time. In order to improve the mixture properties, a binder rejuvenator should be used. Thus, in the present study, the utilization of a used motor oil as a rejuvenator was evaluated. This would allow the modification of the aged binder, restoring some of its original properties and promoting an adequate performance of the mixture. The optimal amount of oil was determined by conventional bitumen tests, using the achievement of a bitumen with a penetration grade above, as the selection criterion for the definition of the amount of oil. Once the amount of rejuvenator (oil) was defined, laboratory specimens were prepared and tested for water sensitivity, permanent deformation, stiffness and fatigue, in order to confirm that the totally recycled mixture will perform as good as a conventional mixture used for comparison purposes.